2016
DOI: 10.1007/s11368-016-1437-y
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and abundance of carbohydrates and amino compounds in sequentially extracted labile soil organic matter fractions

Abstract: Purpose: The study aimed to describe the carbohydrates and amino compounds content in soil, the light fraction (LF), the >53 μm particulate organic matter (POM), and the mobile humic acid (MHA) fraction and to find out whether the carbohydrates and amino compounds can be used to explain the origin of SOM fractions. Materials and methods: Soil samples were collected from two agricultural fields managed under organic farming in southern Italy. The LF, the POM, and the MHA were sequentially extracted from each so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Despite its great importance for soil fertility, the total soil organic carbon (SOC) could not reflect changes of the introduction of organic practices because it often takes years before shifts in agricultural management show detectable variations in SOC content (Clark et al 1998;Yang et al 2019). In contrast, the labile pools of soil organic matter (SOM) are sensitive to short-term changes in management and/or environmental conditions (Haynes 2005), especially the light fraction (LF), the particulate organic matter (POM), and the mobile humic acid (MHA; Abdelrahman et al 2016Abdelrahman et al , 2017Marriott and Wander 2006). The LF is similar chemically to the original plant material, but a lesser amount of carbohydrates (Abdelrahman et al 2016) and a greater quantity of sterols in the LF indicate the early stage of its decomposition in soil (Gregorich et al 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite its great importance for soil fertility, the total soil organic carbon (SOC) could not reflect changes of the introduction of organic practices because it often takes years before shifts in agricultural management show detectable variations in SOC content (Clark et al 1998;Yang et al 2019). In contrast, the labile pools of soil organic matter (SOM) are sensitive to short-term changes in management and/or environmental conditions (Haynes 2005), especially the light fraction (LF), the particulate organic matter (POM), and the mobile humic acid (MHA; Abdelrahman et al 2016Abdelrahman et al , 2017Marriott and Wander 2006). The LF is similar chemically to the original plant material, but a lesser amount of carbohydrates (Abdelrahman et al 2016) and a greater quantity of sterols in the LF indicate the early stage of its decomposition in soil (Gregorich et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the labile pools of soil organic matter (SOM) are sensitive to short-term changes in management and/or environmental conditions (Haynes 2005), especially the light fraction (LF), the particulate organic matter (POM), and the mobile humic acid (MHA; Abdelrahman et al 2016Abdelrahman et al , 2017Marriott and Wander 2006). The LF is similar chemically to the original plant material, but a lesser amount of carbohydrates (Abdelrahman et al 2016) and a greater quantity of sterols in the LF indicate the early stage of its decomposition in soil (Gregorich et al 1996). The POM consists of partially decomposed plant litter, and it acts as a substrate and center for soil microbial activity, a shortterm reservoir of nutrients, a food source for soil fauna, and loci for formation of water stable macroaggregates (Haynes 2005).…”
Section: Introductionmentioning
confidence: 99%
“…and MBN with SSN and quantitatively corresponds to the sum of the hydrochloric acid hydrolysable amino acid N and hydrochloric acid hydrolysable unknown N (Abdelrahman et al, 2016). Some studies have also suggested that it includes amino acids, humic acids, and N-containing heterocyclic compounds bound to minerals (Nannipieri and Eldor, 2009;Wu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the large background of relatively stable C in soil, it is not easy to measure changes in soil total organic C (TOC) in the short term. Soil labile organic C, which is characterized by rapid turnover times and responds quickly, could be regarded as an early indicator of changes in SOC [14,15]. It generally includes particulate organic C (POC), microbial biomass C (MBC), and potassium permanganate-oxidizable C (KMnO 4 -C) [16].…”
Section: Introductionmentioning
confidence: 99%